Evaluation of xerogels of cassava and cocoyam starches as dry granulation binders/disintegrants in directly compressed paracetamol tablet formulations - Sylvester Eraga; Ogochukwu Meko; Magnus Iwuagwu (Mazandaran University of Medical Sciences, 2018)
The physicochemical properties of excipients play vital roles in the process of tablet manufacture. A comparative evaluation of the binding and disintegrant properties of xerogels of cassava and cocoyam starches with microcrystalline cellulose (MCC) in paracetamol tablet formulations was investigated. Cassava and cocoyam starches were extracted from their tubers following standard procedures. Xerogels of both starches were prepared and used to prepare batches of paracetamol granules for direct compression into tablets at concentrations of 3.8, 7.6 and 11.4 %w/w and with 7.6 %w/w MCC for comparison. Granules were analysed for their flow properties and drug-excipient compatibility and the tablets were evaluated for their tablets properties. The paracetamol granules prepared with the xerogel powders were comparable in flow properties with those made with MCC. Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared (FTIR) analyses revealed no interaction between the xerogel powders and paracetamol. Increase in concentrations of the xerogel powders led to an increase in hardness, wetting time, water sorption, disintegration time, drug release and a decrease in friability of the tablets. Tablets formulated with the starch xerogel powders met compendial requirements at 7.6 %w/w concentration. The study confirms the potentials of xerogels of cassava and cocoyam starches as dry granulation binders/disintegrants. Tablets made with the xerogel powders are superior to those made with MCC in terms of disintegration time but MCC produces harder and less friable tablets, as a superior binder.